2019
DOI: 10.17776/csj.526652
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of radioactive pollution in sediment samples of Borçka Dam Lake, Turkey

Abstract: In this research, the concentrations of natural (226Ra, 232Th and 40K) and anthropogenic (137Cs) radionuclides were measured in sediment samples collected from the Borçka Dam Lake using a high purity germanium detector (HPGe). The activity values ranged from 4.79-21.46, 9.36-20.65, 238.01-721.26 and 0.79-6.81 Bq kg-1 for 226Ra, 232Th, 40K and 137Cs respectively. The average 226Ra, 232Th and 40K activity concentrations calculated for the sediment samples were found to be lower compared to world average values r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
(55 reference statements)
2
0
0
Order By: Relevance
“…But procuration should be taken to avoid increase in radionuclides concentration in the nearest further. The values obtained in comparison with similar coastal environment of other countries and part of Nigeria, shows that the values are in agreement with those reported in literatures [ [40] , [41] , [54] ]. Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…But procuration should be taken to avoid increase in radionuclides concentration in the nearest further. The values obtained in comparison with similar coastal environment of other countries and part of Nigeria, shows that the values are in agreement with those reported in literatures [ [40] , [41] , [54] ]. Fig.…”
Section: Resultssupporting
confidence: 92%
“…The obtained means concentrations of 40 K, 238 U and 232 Th in the study area exceeded both the values of the control and world standard limit of 400 Bqkg −1 , 35 Bqkg −1 and 30 Bqkg −1 respectively [ 38 ]. Similarly, the concentrations of 40 K, 238 U and 232 Th in the present study was found higher than those reported elsewhere around the world [ [4] , [5] , [6] , [22] , [24] , [25] , [26] , [37] , [39] , [40] , [41] , [42] ] but compared favorably with results reported by Refs. [ 43 , 44 ].…”
Section: Resultssupporting
confidence: 80%